The Integrasi Pemberdayaan Perempuan Dalam Meningkatkan Kesejahteraan Masyarakat Di Desa Ujung Serdang, Kabupaten Deli Serdang - Pakpahan, Rugun Elis Deoktavia; Hodriani, Hodriani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2025)
Women's empowerment is an effort to encourage and improve the ability of women to be more empowered. However, in its implementation, there are often challenges that go unnoticed, such as traditional stereotypes that place women solely as housekeepers. This is often a barrier to women's participation in social and economic activities. This research aims to examine the role of women's empowerment in efforts to improve community welfare in Ujung Serdang Village. This research uses a qualitative method with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation. The research subjects included the Head of Ujung Serdang Village and housewives. The results showed that the women's empowerment program in Ujung Serdang Village succeeded in improving community welfare through skills training and support from village institutions. Although faced with obstacles such as the burden of multiple roles and traditional views, women are still able to increase their income and family economic independence. To ensure the sustainability of the program, strong cooperation between the village government, the village government, and the village government is needed. To ensure the sustainability of the program, strong cooperation between the village government, family, and community is needed to support women's empowerment.